(untitled) (Journal of Hama University, 2019)
The objective of this study is to investigate the effect of sickle cell anemia (SCA) on oral health in children and adolescents in Syria. The sample consisted of 274 subjects, aged between 8 and 17 years, divided into two equal and matched groups, which are SCA patients group and control group. We examined and evaluated the oral health using the following indices (DMFT to exam caries in permanent dentation, gingival index GI, and plaque index PI). Result: Statistically significant differences were apparent in all of the measured variables. DMFT, GI, PI were high in SCA group when compared to the control group. Conclusion: The current study showed that SCA patients are more susceptible to have Poor oral hygiene.